1996
DOI: 10.1144/petgeo.2.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir monitoring of the Magnus Field through 4D time-lapse seismic analysis

Abstract: During 10 years of production, crestal fluid pressures in the Magnus Field (UKCS) have dropped from 6650 psi to under 3500 psi leading to a two- to three-fold increase in the effective stress on the rock fabric. Petroacoustic measurements on cores indicate that this leads to a 12% increase in the acoustic impedance which, in theory, should be detectable using time-lapse seismic data. We analyse the difference between two 3D surveys shot over Magnus and relate this to dynamic changes in fluid pressure and satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…The average increase in P-wave impedance is 4% (standard deviation is 1% based on all 29 core samples) for a pore pressure drop of 40 bars. This is in contrast to, for example, the Magnus study (Watts et al 1996), where greater pore pressure drops were expected and confirmed by the repeated seismic data. Figure 3 summarizes the main results of the rock physics feasibility study, and shows that, according to the Gassmann model and the ultrasonic core measurements, we expect that fluid saturation changes have a stronger impact on seismic parameters than the pore pressure decrease (8% compared to 4% for acoustic impedance, for instance).…”
Section: Feasibility Studysupporting
confidence: 61%
See 1 more Smart Citation
“…The average increase in P-wave impedance is 4% (standard deviation is 1% based on all 29 core samples) for a pore pressure drop of 40 bars. This is in contrast to, for example, the Magnus study (Watts et al 1996), where greater pore pressure drops were expected and confirmed by the repeated seismic data. Figure 3 summarizes the main results of the rock physics feasibility study, and shows that, according to the Gassmann model and the ultrasonic core measurements, we expect that fluid saturation changes have a stronger impact on seismic parameters than the pore pressure decrease (8% compared to 4% for acoustic impedance, for instance).…”
Section: Feasibility Studysupporting
confidence: 61%
“…The results from different 4D seismic case studies so far indicate that the areal consistency of various seismic features is robust with respect to noise, and useful information can be obtained even if the baseline survey is old. Some recent examples from the North Sea are the Oseberg study (Johnstad et al 1995), the Magnus time lapse study (Watts et al 1996), the Fulmar study (Johnston et al 1997). Earlier presentations of the Gullfaks 4D study can be found in Sønneland et al (1997).…”
Section: Introductionmentioning
confidence: 99%
“…A typical application of time-lapse seismic data for monitoring temporal changes in reservoir properties is mainly based on assessment of changes in seismic reflection amplitudes (Watts et al 1996;Landrø et al 1999). However, seismic amplitude differences can get entangled with time-shifts, as illustrated in Figures 3 and 4.…”
Section: E T H O D O L O G Ymentioning
confidence: 99%
“…4-D seismic imaging is now routinely exploited in the oil and gas industry to monitor production effects within hydrocarbon reservoirs (Watts et al, 1996;Lumley, 2001;Tura et al, 2005;Fomel and Jin, 2009), as well as in supervising CO 2 sequestrations (Chadwick et al, 2005;Lumley, 2010).…”
Section: Time-lapse Seismic Monitoringmentioning
confidence: 99%